Age-based challenges to type 1 diabetes management in the pediatric population - Lan, Yung-Yi; Kovinthapillai, Rujith; Kędzia, Andrzej; Niechciał, Elżbieta (Frontiers in Pediatrics, 2024)
Type 1 diabetes is rising in the pediatric population, affecting approximately 1.2 million children and adolescents globally. Its complex pathogenesis involves the interaction between genetic predisposition and environmental factors, leading to T cell-mediated destruction of insulinproducing pancreatic beta-cells. This destruction results in insulin insufficiency and hyperglycemia. Hence, managing type 1 diabetes requires a comprehensive approach that includes various aspects such as blood glucose monitoring, insulin therapy, carbohydrate counting, caloric intake monitoring, considering family habits and food preferences, planning daily schedules, and incorporating physical activity. Children with type 1 diabetes encounter age-specific challenges in disease management that may exacerbate the risk of metabolic complications and adverse health outcomes. These risk factors may be neurological, physiological, behavioral, psychological, or social, complicate management and necessitate tailored approaches for effective care. Regardless of the age group, primary caregivers have a high responsibility to maintain optimal glycemic control, including monitoring diet, daily activity, and administering insulin. By reviewing research on the challenges faced by pediatric patients with type 1 diabetes, we summarized key insights aimed at developing targeted interventions and support systems that enhance diabetes management and improve health outcomes in this vulnerable population.